Improving Antibiotic Prescribing for Children With Urinary Tract Infection in Emergency and Urgent Care Settings. Issue 6 (June 2020) - Poole, Nicole M.; Kronman, Matthew P.; Rutman, Lori; Weissman, Scott J.; Migita, Russell T.; Caglar, Derya; Zerr, Danielle M.
Abstract : Objectives: Children with urinary tract infection (UTI) are often diagnosed in emergency and urgent care settings and increasingly are unnecessarily treated with broad-spectrum antibiotics. This study evaluated the effect of a quality improvement intervention on empiric antibiotic prescribing for the treatment of uncomplicated UTI in children. Methods: A local clinical pathway for uncomplicated UTI, introduced in June 2010, recommended empiric treatment with cephalexin, a narrow-spectrum (first-generation) cephalosporin antibiotic. A retrospective quasi-experimental study of pediatric patients older than 1 month presenting to emergency and urgent care settings from January 1, 2009, to December 31, 2014, with uncomplicated UTI was conducted. Hospitalized patients and those with chronic conditions or urogenital abnormalities were excluded. Control charts and interrupted time-series analysis were used to analyze the primary outcome of narrow-spectrum antibiotic prescribing rates and the balancing measures of 72-hour revisits, resistant bacterial isolates, and subsequent inpatient admissions for UTI. Results: A total of 2134 patients were included. There was an immediate and sustained significant increase in cephalexin prescribing before (19.2%) versus after (79.6%) pathway implementation and a concurrent significant decline in oral third-generation cephalosporin (cefixime) prescribing from 50.3% to 4.0%. There was no significant increase in 72-hour revisits, resistant bacterial isolates, or inpatient admissions for UTI. Conclusions: A clinical pathway produced a significant and sustained increase in narrow-spectrum empiric antibiotic prescribing for pediatric UTI. Increased empiric cephalexin prescribing did not result in increased treatment failures or adverse patient outcomes. Future studies on implementing clinical pathways for children outside a pediatric hospital network are needed. Abstract : Supplemental digital content is available in the text.